TINDAK PIDANA KEIMIGRASIAN TERHADAP PENYALAHGUNAAN IZIN TINGGAL BAGI ORANG ASING KOTA SAMARINDA MENURUT UNDANG - UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN - Jeffry Sanjaya (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT           This study entitled "Immigration Crime Against Abuse Residence Permit For Foreigners Samarinda According to Constitusin No. 6 of 2011 Concerning Immigration”. Core issues that were examined in this study are: first, how the legal action against the abuse of residence permits for foreigners Samarinda according to Constitusion No. 6 of 2011 on Immigration? second, what the Roles and Responsibilities of Class I Immigration Office Samarinda City related to Constitusion No. 6 of 2011 on Immigration? Based on the core of the problem above, the purpose of this study are: first, to know how the legal action against the abuse of residence permits for foreigners in the city of Samarinda, according to Constitusion No. 6 of 2011. Second, to find out what the roles and responsibilities of Class I Immigration Office in Samarinda relating to Constitusion No. 6 of 2011. This study is included normative juridical research, namely by reviewing the related licensing, regulations applicable law, including the norms and principles contained therein. Data was collected through library research and field research. Data analysis is done by juridical qualitative, ie the research results contained in the form of descriptive narrative  From the data can Authors gather the data obtained as follows: Repression deportation against the misuse of permit to live in the city of Samarinda Period In 2015 as many as 15 foreigners, in January - June 2016 the Immigration Office of Samarinda issued at least issued 90 temporary stay permits to foreigners, while foreigners who are deported as a result of misuse of permit to live in the city of Samarinda many as 3 people.          On the basis of these conclusions, the author proposes suggestions: first, Immigration Office Class I Samarinda need to increase human resources (HR) in quantity to form and train civil servant investigators (investigators) in the framework of action strangers .. Secondly, coordination between the Office Expected immigration Class I Samarinda with relevant agencies further enhanced to optimize the supervision of foreigners and measures of intelligence operations. Keywords: Immigration Crime, Constitusion No. 6 of 2011.